Diagnostic stability and outcome after first episode psychosis - Gale-Grant, Oliver; Dazzan, Paola; Lappin, Julia M.; Donoghue, Kim; Reininghaus, Ulrich; Croudace, Tim; Jones, Peter B.; Murray, Robin; Fearon, Paul; Doody, Gillian A.; Morgan, Craig; Heslin, Margaret (Journal of mental health, 2021)
Individuals diagnosed with schizophrenia are often assigned other psychiatric diagnoses during their lives. The significance of changing diagnosis has not been widely studied. Our aim was to examine the association between diagnostic change and later outcome. Individuals’ diagnostic history, clinical and social outcomes were extracted from the AESOP-10 study, a 10-year follow-up of first episode psychosis cases. The association between outcome and different patterns of diagnosis over time were assessed using linear or logistic regression. Individuals always diagnosed with schizophrenia (n = 136) had worse clinical and social outcomes at follow-up than those never diagnosed with schizophrenia (n = 163), being more likely to be symptomatic, unemployed, single, and socially isolated. There was no difference in outcome between individuals always diagnosed with schizophrenia and those changing to a diagnosis of schizophrenia (n = 60), and no difference in outcome between individuals never diagnosed with schizophrenia, and those changing from a diagnosis of schizophrenia (n = 44). Individuals always and never diagnosed with schizophrenia had different outcomes. In cases of diagnostic instability participants had similar outcomes to those always assigned the diagnosis they changed to irrespective of initial diagnosis.
Online publiziert: 22. September 2020
Gesehen am 12.09.2025